2014
DOI: 10.4103/0976-7800.141187
|View full text |Cite
|
Sign up to set email alerts
|

Menopause and oral health

Abstract: Different phases of a woman's life: Puberty, menses, pregnancy, and menopause have varied influence on her oral health. During the menopause, women go through biological and endocrine changes, particularly in their sex steroid hormone production, affecting their health. Because the oral mucosa contains estrogen receptors, variations in hormone levels directly affect the oral cavity. A few oral conditions and or diseases are seen more frequently during post menopausal years. Role of hormones affecting the healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 44 publications
4
72
0
4
Order By: Relevance
“…But the mucosa is affected by age, increasing xerostomia and reducing periodontal health 14,21,85, [87][88][89] . A recent study revealed that the low level of dehydroepiandrosterone (DHEA) in these patients may contribute to the etiopathogeny of BMS 90 .…”
Section: Menopausementioning
confidence: 99%
“…But the mucosa is affected by age, increasing xerostomia and reducing periodontal health 14,21,85, [87][88][89] . A recent study revealed that the low level of dehydroepiandrosterone (DHEA) in these patients may contribute to the etiopathogeny of BMS 90 .…”
Section: Menopausementioning
confidence: 99%
“…Влияние половых стероидных гормонов на процессы ремоделирования специализи-рованных оральных тканей, на сегодняшний день, подтверждено многочисленными иссле-дованиями [4,7,8].…”
Section: Introductionunclassified
“…Variations in hormone levels directly affect the oral cavity as oral mucosa contains estrogen receptors. Oral mucosa resembles with vaginal mucosa in its histology as well as its response to estrogen hormone [11]. Praklinna dwija denotes the same (healthy periodontal tissues/oral cavity).…”
Section: Praklinna Dwija (Moist Gums/healthy Oral Cavity/ Healthy Permentioning
confidence: 99%